16S rRNA‐targeted oligonucleotide probes for direct detection of Propionibacterium freudenreichii in presence of Lactococcus lactis with multicolour fluorescence in situ hybridization. (1st September 2014) - Mikš‐Krajnik, M.; Babuchowski, A.
Abstract: Multicolour fluorescence in situ hybridization (FISH) has been applied to detect Lactococcus lactis and Propionibacterium freudenreichii cells in mixed populations in medium and skimmed milk, using epifluorescent microscopy. The 16S rRNA‐targeted 18‐mer oligonucleotide probes, specific for P. freudenreichii were designed and evaluated. Based on multiple alignments of designed sequences, eight 16S rRNA probes were selected for in vitro studies. The permeabilization protocol was optimized for simultaneous hybridization of propionibacteria and lactococci cells. The probes GLO62 ( 62‐80 ), PEU64 ( 64‐82 ) and PFX311 ( 311‐329 ) were found specific for P. freudenreichii in analysis in vitro . Lactococcus lactis cells were labelled with LactV5 ( 822‐840 ), (S‐S‐L.lact‐0821‐a‐A‐18) probe. The following combinations of oligonucleotide probes: LactV5/GLO62, LactV5/PEU64 and LactV5/PFX311, enabled differentiation of Lc. lactis and P. freudenreichii cells in culture media and in skimmed milk. Significance and Impact of the Study: Results showed that three newly designed 16S rRNA‐targeted oligonucleotide probes specific for Propionibacterium freudenreichii in combination with a probe specific for Lactococcus lactis can be used to differentiate lactic and propionic acid bacteria in mixed communities using multicolour fluorescence in situ hybridization (FISH), without applying permeabilization step. This is a first study on simultaneous detection of both bacterial species with FISH, which was found as rapid, useful and culture‐independent tool for direct visualization of bacteria on single cell level. It might be applied in monitoring of mixed starter cultures in dairy industry.